2021
DOI: 10.3389/fimmu.2021.779100
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Selective Cytokine Signaling Inhibition by Antibodies Targeting a Shared Receptor

Abstract: Interleukin-1 (IL-1) family cytokines are potent mediators of inflammation, acting to coordinate local and systemic immune responses to a wide range of stimuli. Aberrant signaling by IL-1 family cytokine members, however, is linked to myriad inflammatory syndromes, autoimmune conditions and cancers. As such, blocking the inflammatory signals inherent to IL-1 family signaling is an established and expanding therapeutic strategy. While several FDA-approved IL-1 inhibitors exist, including an Fc fusion protein, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The calculation of HDX data from a protein atomic models based on the phenomenological expression is now feasible for researchers using a software package called HDX ensemble reweighing (HDXer) developed by Bradshaw et al (93). In a recent study, this technique was applied to simulate the deuterium uptake of the top docking poses to compare with the experimental data (36). The simulated HDX profiles of the two docking complexes aligned well with the empirical data, further validating the selected models, and highlighting the advances being made in the field of HDX prediction.…”
Section: Many Different Methods Have Been Developed To Predict Pf Fro...mentioning
confidence: 99%
See 3 more Smart Citations
“…The calculation of HDX data from a protein atomic models based on the phenomenological expression is now feasible for researchers using a software package called HDX ensemble reweighing (HDXer) developed by Bradshaw et al (93). In a recent study, this technique was applied to simulate the deuterium uptake of the top docking poses to compare with the experimental data (36). The simulated HDX profiles of the two docking complexes aligned well with the empirical data, further validating the selected models, and highlighting the advances being made in the field of HDX prediction.…”
Section: Many Different Methods Have Been Developed To Predict Pf Fro...mentioning
confidence: 99%
“…HDX-MS has been used successfully in the past to map Ab epitopes to Ag surfaces (e.g., 14,20,22,28,[31][32][33][34][35][36]. A typical HDX-MS epitope mapping experiment (Figure 1) is performed on the Ag alone as a reference and then in complex with the Ab.…”
Section: Hdx-ms Experimental Approach and Data Processing For Ab-ag S...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the specific role of IL-33/ST2 axis that might predominate in tumor remains to be further studied. Ongoing phase II clinical studies (NCT03267316 and NCT05116891) on IL-1RAcP antibody CAN04, which showed the potency of selective cytokine signaling inhibition of IL-1 family cytokines in NSCLC ( 62 ), may hopefully find a new method to treat lung cancer.…”
Section: An Overview Of Il-33mentioning
confidence: 99%